Simulation-optimization framework in urban flood management for historic and climate change scenarios. Issue 2 (21st December 2021) - Madhuri, R.; Sarath Raja, Y. S. L.; Srinivasa Raju, K.
Abstract: A simulation-optimization framework is established by integrating Hydrologic Engineering Center Hydraulic Modeling System (HEC-HMS) for computation of runoff, siting tool EPA System for Urban Storm-water Treatment and Analysis INtegration (EPA-SUSTAIN) for placement of Best Management Practices (BMPs), and Binary Linear Integer Programming (BLIP) for runoff reduction. The framework is applied to an urban catchment, namely Greater Hyderabad Municipal Corporation (GHMC). The rainfall-runoff analysis was conducted for extreme rainfalls for historic (2016) and future events in 2050 and 2064 under Representative Concentration Pathways (RCPs) 6.0 and 8.5. The simulation-optimization approach in the historic scenario yielded 495, 607 BMPs occupying 76.99 km 2 resulting in runoff reduction of 21.54 mm (198.76–177.22 mm). Achieved runoff reduction is 38.72 (428.35–389.63 mm) and 55.03 (602.65–547.62 mm), respectively, for RCPs 6.0 and 8.5, which could meet the water demands of GHMC for 10.33 and 11.53 days. Impacts of 10 different BMP configurations of varying costs (10–70%) and pollutant load reductions (0–3%) on runoff reduction are accomplished as part of sensitivity analysis. HIGHLIGHTS: Simulation-optimization framework for best management practices to an urban catchment of GHMC for historic and two RCP-based extreme event rainfall scenarios. Studying the applicability of EPA-SUSTAIN BMP siting tool, screening procedure, and BLIP for placement of BMPs for historic rainfall event and two RCP-based extreme event rainfall scenarios. Flood preparedness by implementing BMPs in an urbanized catchment.